Low-Power Active Interference Cancellation for OFDM Spectrum Sculpting - Schmidt, J.F.; Daniel Romero; R. López-Valcarce (European Signal Processing Conference (EUSIPCO), 2014)
We present a low-power design for Active Interference Cancellation (AIC) sculpting of the OFDM spectrum, based on sparse design concepts. Optimal AIC designs compute cancellation weights based on contributions from all data subcarriers. Thus, as the number of subcarriers grows, power consumption becomes a concern, and suboptimal solutions that avoid involving all subcarriers are of interest. In this context, we present novel sparse AIC designs based on a zeronorm minimization of the matrix defining the cancellation weights. These designs drastically reduce the number of operations per symbol, and thus the power consumption, while allowing to tune the loss with respect the optimal design. They can be efficiently obtained and significantly outperform usual thresholding or sparsity-inducing l_1-norm minimization approaches.